Linguistic impoliteness in (translated) children's fiction - Pleyer, Monika (DASK - Duisburger Arbeiten Zur Sprach- und Kulturwissenschaft / Duisburg Papers on Research in Language and Culture Ser., 2022)
This book presents the first large-scale investigation of the structure and functions of linguistic impoliteness and impoliteness metalanguage in contemporary British children's fiction. The study ties together findings from pragmatics, language acquisition research, literary studies, and translation studies with novel data-driven insights.